Pengaruh Working Capital Turnover dan Return On Equity terhadap Nilai Perusahaan - Jumi Syafutri, Rika Riski; Abdurrahman, Abdurrahman; Wijaya, Trisnadi (MDP Student Conference, 2025)
This study aims to analyze the effect of Working Capital Turnover (WCTO) and Return on Equity (ROE) on firm value. The research data used is secondary data, consisting of financial statements and annual reports. The sample in this study consists of industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period, totaling 43 companies. The sampling technique used is purposive sampling. The results of the study indicate that Working Capital Turnover has no effect on firm value, whereas Return on Equity has an impact on firm value."